Refining the Formation and Early Evolution of the Eastern North American Margin: New Insights From Multiscale Magnetic Anomaly Analyses. Issue 11 (16th November 2017) - Greene, John A.; Tominaga, Masako; Miller, Nathaniel C.; Hutchinson, Deborah R.; Karl, Matthew R.
Abstract: To investigate the oceanic lithosphere formation and early seafloor spreading history of the North Atlantic Ocean, we examine multiscale magnetic anomaly data from the Jurassic/Early Cretaceous age Eastern North American Margin (ENAM) between 31 and 40°N. We integrate newly acquired sea surface magnetic anomaly and seismic reflection data with publicly available aeromagnetic and composite magnetic anomaly grids, satellite‐derived gravity anomaly, and satellite‐derived and shipboard bathymetry data. We evaluate these data sets to (1) refine magnetic anomaly correlations throughout the ENAM and assign updated ages and chron numbers to M0–M25 and eight pre‐M25 anomalies; (2) identify five correlatable magnetic anomalies between the East Coast Magnetic Anomaly (ECMA) and Blake Spur Magnetic Anomaly (BSMA), which may document the earliest Atlantic seafloor spreading or synrift magmatism; (3) suggest preexisting margin structure and rifting segmentation may have influenced the seafloor spreading regimes in the Atlantic Jurassic Quiet Zone (JQZ); (4) suggest that, if the BSMA source is oceanic crust, the BSMA may be M series magnetic anomaly M42 ( 168.5 Ma); (5) examine the along and across margin variation in seafloor spreading rates and spreading center orientations from the BSMA to M25, suggesting asymmetric crustal accretion accommodated the straightening of the ridge from the bend in the ECMA to the more linear M25; and (6) observe anomalously high‐amplitude magnetic anomalies near the Hudson Fan, which may be related to a short‐lived propagating rift segment that could have helped accommodate the crustal alignment during the early Atlantic opening. Key Points: Newly identified marine magnetic anomalies document the formation and evolution of the ENAM and western North Atlantic Ocean Early Atlantic seafloor spreading rates and ridge orientations indicate possible asymmetric crustal accretion Early seafloor spreading may have been influenced by preexisting margin structure and may have included short lived propagating rifts